Formulation of Healthy Noodle with the Addition of Moringa Leaf Extract (Moringa Oliefera L.) as an Alternative Food to Reduce Uric Acid - agustina dyah setyowati; ihat solihat; Nandhasari Nandhasari; yunita aninda (Jurnal Ilmiah Teknik Kimia, 2023)
Moringa leaves (Moringa oleifera L.) belong to the Moringaceae family which can live in both highland and lowland areas. Moringa leaves have high nutrition so they have the potential to be used as a food-making mixture. The purpose of this study was to determine the effect of noodles with a mixture of Moringa leaf extract on gout sufferers and to determine the effect of Moringa leaf extract on noodles from the results of the water content test, protein test, and organoleptic test. In this study, the treatment was a comparison between wheat flour and Moringa leaf flour, namely sample A (125:0), sample B (120:5), and sample C (115:10). Each test treatment was repeated 3 times. The results of the protein test research are Samples A, B, and C contained protein compounds. The results of the water content test are Sample A 59%, and sample B 55.6%. and sample C 52%. The results of organoleptic test research conducted on 15 respondents, noodles with a mixture of Moringa leaf powder sample B were the most popular noodle product by respondents. The conclusion shows that the addition of Moringa leaf flour affects the water content, protein test, and organoleptic of wet noodles. As well as the test results of the effect of noodles with a mixture of Moringa leaf extract on gout sufferers showed that uric acid levels after consuming noodles with a mixture of Moringa leaf extract every day for a month, namely in consumer 1, decreased by 39% and in consumer 2, it decreased by 29%.